Changes in soil and vegetation with stabilization of dunes in a desert–oasis ecotone. Issue 4 (17th April 2015) - Wang, Guohua; Zhao, Wenzhi; Liu, Hu; Zhang, Gefei; Li, Fang
Abstract: Revegetation of indigenous plants in a desert–oasis ecotone is an effective way of maintaining the stability of oases. Understanding the changes in vegetation and soil is crucial for restoration management. The properties of soil and vegetation at stabilized sites of different ages were investigated in a typical desert–oasis ecotone, located in the Hexi Corridor region in arid northwestern China, over a period of 40 years. The results indicated that after 40 years the organic matter, total‐N and available‐P at 0–2 cm soil depth increased from 0.1, 0.1 g kg −1, 7 mg kg −1 to 2.0, 0.9 g kg −1, and 75 mg kg −1, respectively. At 2–5 cm the organic matter, total‐N and available‐P increased from 0.4, 0.1 g kg −1, and 7 mg kg −1 to 2.3, 0.4 g kg −1, and 38 mg kg −1, respectively. The number of herbaceous species increased from 4 to 9 and the herbaceous cover increased from 6 to 28 % after 40 years. The height and cover of the sand‐binding vegetation Haloxylon ammodendron ( H. ammodendron ) reached the highest levels of 446 cm and 68 % after 25 years. After 35 years H. ammodendron dwindled and its belowground and aboveground biomass both decreased significantly. With effective natural regeneration, after 40 years the population of H. ammodendron remained stable and its cover and density remained at 38 % and 1870 ha −1 respectively. The positive mutual feedback between vegetation and soil permitted the sand‐binding vegetation community to become stable over time.